Troubling stoicism: Sociocultural influences and applications to health and illness behaviour. (March 2013) - Moore, Andrew; Grime, Janet; Campbell, Paul; Richardson, Jane
In light of the ambiguity of meanings attributed to the concept of stoicism we critically explore its use as a label to explain and describe health and illness behaviour, juxtaposing the often negative portrayals of contemporary stoicism against its classical and philosophical origins. By reflecting critically on the term 'stoicism', its application and dimensionality, we show how the term has evolved from classical to contemporary times in relation to changing context, and explore different understandings of the term across medical and health literature. We attend to sociocultural factors that are seen to influence the conceptualization of stoicism such as generational influences, gender and geographies. We make the assertion that by applying the label of 'stoicism' as it is known today, there is a danger of too readily accepting a term that masks particular health behaviours while missing an array of sociological factors that are important to how people deal with adversity arising from chronic health problems. We therefore encourage further questioning of this term.